Reproductive Technology and the Child Care Sector: How Access to Oral Contraception and Abortion Shaped Workforce Composition and Quality - Chris M. Herbst; Erdal Tekin (Institute of Labor Economics (IZA), 2025)
The composition and quality of the child care workforce may be uniquely sensitive to changes in the complementarities between home production and market work. This paper examines whether the expansion of oral contraceptives and abortion access throughout the 1960's and 1970's influenced the composition, quality, and wages of the child care workforce. Leveraging state-by-birth cohort variation in access to these reproductive technologies, we find that they significantly altered the educational profile of child care workers—increasing the proportion of less-educated women in the sector while reducing the share of highly-educated workers. This shift led to a decline in average education levels and wages within the child care workforce. Furthermore, access to the pill and abortion influenced child care employment differently across settings, with center-based providers losing more high-skilled workers to alternatives with better career opportunities, and home-based and private household providers absorbing more low-skilled women, for whom child care may have remained a viable employment destination. Overall, our findings indicate that increased reproductive autonomy, while expanding women's access to higher-skilled and -paying professions, also resulted in a redistribution of skilled labor away from child care, which may have implications for service quality, child development, and parental employment.
Keywords: I21; I38; J13; J22; J24; 330; abortion; child care; pill; contraceptive; reproductive technology